2019
DOI: 10.1101/722637
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gi-Coupled Receptor Activation Potentiates Piezo2 Currents via Gβγ

Abstract: SUMMARYDysregulation of mechanosensitive Piezo2 channels is a hallmark of mechanical allodynia, yet the cellular mechanisms that sensitize mechanoreceptors are still poorly understood. Activation of Gi-coupled receptors sensitizes Piezo2 currents, but whether Gi-coupled receptors regulate the activity of Piezo2 channels is not known. Here, we found that activation of Gi-coupled receptors potentiates Piezo2 currents in dorsal root ganglion (DRG) neurons and in heterolo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
(74 reference statements)
1
3
0
Order By: Relevance
“…We considered currents to be rapidly adapting, if they fully inactivated before end of the 200 ms mechanical stimulus. The inactivation time constants (tau) of these currents were 17.95 ± 2.4 ms, similar to that in our earlier work (Borbiro et al, 2015; Del Rosario et al, 2020). Intermediate adapting currents did not fully inactivate, but the leftover current at the end of the mechanical simulation was less that 50% of the peak current.…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…We considered currents to be rapidly adapting, if they fully inactivated before end of the 200 ms mechanical stimulus. The inactivation time constants (tau) of these currents were 17.95 ± 2.4 ms, similar to that in our earlier work (Borbiro et al, 2015; Del Rosario et al, 2020). Intermediate adapting currents did not fully inactivate, but the leftover current at the end of the mechanical simulation was less that 50% of the peak current.…”
Section: Methodssupporting
confidence: 90%
“…DRG neurons were isolated as described previously (Borbiro et al, 2015; Del Rosario et al, 2020). All animal procedures were approved by the Institutional Animal Care and Use Committee at Rutgers NJMS.…”
Section: Methodsmentioning
confidence: 99%
“…Co-activation of both 5-HT1A and 5-HT2A in cortical pyramidal neurons leads to complex physiologic responses [ 65 , 66 ] that are further regulated by 5HT1A receptors on local inhibitory neurons [ 67 ]. The effects of receptor activation can also vary depending on inputs from other neuromodulators [ 68 ] and the differential activation of downstream effectors [ 65 , 69 ].These studies highlight the difficulties of predicting the effects of serotonin receptor activation based solely on expression data, and the need for physiological assays to assess their role in specific circuits. Although two recent studies have reported serotonin receptor expression in visual neurons [ 70 , 71 ], to our knowledge there is no information on the physiological effect(s) of any serotonin receptor in any of the interneurons within the insect visual system.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that MAPK pathways can modulate Piezo2 currents (Doihara et al, 2009b). In addition, literature suggests that AS-IV has antiinflammatory properties by inhibiting the phosphorylation of ERK1/2 and p38 in various diseases, such as atherosclerosis and hepatic steatosis (Gao et al, 2017;Del Rosario et al, 2020;Chen et al, 2021). Therefore, we investigated the activation of MAPK pathways in mouse colon and observed a significant increase in p-p38 and p-ERK levels in STC tissue, while their expression decreased in the Lop + AS group.…”
Section: Discussionmentioning
confidence: 89%